ONTOLOGI TERORISME DALAM PERSPEKTIF FILSAFAT EKSISTENSIALISME GABRIEL H. MARCEL - Wikandaru, Reno (Jurnal Filsafat "WISDOM", 2014)
Terrorism is one of the most terrible crimes. Various efforts have been conducted by the government, however, until now terrorism is still a serious issue. As a human behavior, the crime of terrorism is one thing that can be analized from various perspectives, as well as from the existentialism philosophy framework of Gabriel H. Marcel as described in this article. In relation to the analysis of terrorist behavior in Indonesia, it can be concluded that acts of terrorism, espe- cially those committed by suicide bombings, are ontologically behavioral parts of human chosen efforts to achieve "Being", which also involves meeting between "I" and "You". Regardless of any deed done (in terms of material deeds), in Marcel's perspective, such deeds are formally examples of "human" acts be- cause of the "procedure" passed by the terrorist according to the phases pro- posed by Marcel. Although it may be a barbaric act, but judging from the formal side of the decision he chooses, the perpetrator of terror is the actor who attains "Being" because he finds the presence of "Thou" in the decisions he takes.